Strategi Ekspansi Internasional dan Adaptasi Pemasaran Ritel: Studi Kasus Kenangan Coffee Malaysia (Kopi Kenangan Group) - Enty Evasari Simanjuntak (Jurnal Ekonomi Bisnis dan Kewirausahaan, 2026)
The rapid growth of the coffee chain industry in Southeast Asia encourages companies to expand internationally to increase market reach and competitiveness. This study aims to analyze the international expansion strategy and marketing adaptation implemented by Kopi Kenangan during its initial entry into Malaysia under the brand name Kenangan Coffee. The research employed a qualitative method with a descriptive case study approach and a desk-based research design. Data were collected from company press releases, business media reports, industry publications, and relevant academic literature, then analyzed through data reduction, SWOT analysis, marketing mix (4P) evaluation, and source triangulation. The findings indicate that Kenangan Coffee's expansion is supported by internal strengths—including strong brand identity, digital technology utilization, and strategic store locations—as well as external opportunities arising from cultural proximity and modern coffee consumption trends. The company adopts a hybrid marketing strategy by maintaining core product quality while adapting its product, pricing, place, and promotion strategies to suit the Malaysian market. This study implies that combining marketing adaptation with digital technology plays an important role in supporting retail brand internationalization.